Analisis terhadap Penyelundupan Hukum dalam Perjanjian dan Irisannya dengan Penyalahgunaan Keadaan dan Perbuatan Melawan Hukum - Soraya Firmansjah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
This research analyzes legal smuggling related to the principle of freedom of contract reflected in Book III of the Civil Code. The parties are free to draft any clause based on an agreement. However, it cannot be denied that the principle of freedom of contract is often misused to commit legal smuggling in agreements, which makes the deal seem legally valid, even though there are mixed legal provisions, thus causing irregularities and losses for parties who are in a weak position. This research method uses normative legal research by examining library materials with legal materials, such as laws and regulations, books, legal journals, and legal articles. The results of this study indicate that the actions taken by the dominant party, in this case, fulfill the elements of legal smuggling which also intersect with the act of abuse of circumstances, thus forming a tort committed by the dominant party in the agreement.